PERAN PENDIDIKAN AGAMA DALAM MEMBENTUK KARAKTER SUMBER DAYA MANUSIA: SEBUAH TINJAUAN PUSTAKA - Fikri, Muhammad; Malihah, Lola (AL-FALAH: Jurnal Keislaman dan Kemasyarakatan, 2024)
Abstract One of the main objectives of national education is to increase piety to God Almighty. In order to achieve this goal, the role of religious education becomes very strategic. Schools as formal institutions that organize educational activities must have objectives that are in line with the goals of national education. This paper is a literature review that aims to analyze the role of religious education in the formation of human resource character. The data in this paper is in the form of secondary data obtained from literature data in the form of books, articles and previous research results that have been published in scientific journals. The findings in this paper are in the form of the role of schools as formal educational institutions that provide education, the role of teachers who teach religious education plays a role in shaping the character of students. Religious education teaches faith, obedience, and worship procedures, teaches moral formation and example that will become a habit. Discipline, mutual respect, respect and tolerance behavior are very important to be applied from early education. In order to become a habit that will always be applied by students wherever they will be. Of course, good habits are not only for now, but will continue to be carried out sustainably in the future. So that it will produce a quality next generation of the nation.  Keywords: Character Building, Human Resources, Religious Education. AbstrakSalah satu tujuan utama pendidikan nasional adalah meningkatkan ketakwaan kepada Tuhan Yang Maha Esa. Dalam rangka mencapai tujuan tersebut peran pendidikan agama menjadi sangat strategis. Sekolah sebagai lembaga formal yang menyelenggarakan kegiatan pendidikan harus memiliki tujuan yang sejalan dengan tujuan pendidikan nasional tersebut. Tulisan ini merupakan sebuah tinjauan pustaka yang bertujuan untuk menganalisis peran pendidikan agama dalam pembentukan karakter sumber daya manusia. Data dalam tulisan ini berupa data sekunder yang diperoleh dari data kepustakaan berupa buku, artikel dan hasil penelitian terdahulu yang telah dipublikasikan di jurnal ilmiah. Temuan dalam tulisan ini berupa peran sekolah sebagai lembaga pendidikan formal yang menyelenggarakan pendidikan, peran guru yang mengajarkan pendidikan agama sangat berperan dalam pembentukan karakter peserta didik. Pendidikan keagamaan mengajarkan keimanan, ketaatan, beserta tata cara ibadahnya, mengajarkan pembinaan akhlak dan keteladanan yang akan menjadi sebuah kebiasaan. Perilaku disiplin, saling menghargai, menghormati dan perilaku toleransi sangat penting untuk diterapkan sejak pendidikan dini. Agar menjadi sebuah kebiasaan yang akan selalu diterapkan peserta didik dimana pun nanti berada. Tentunya kebiasaan baik itu bukan hanya untuk saat ini saja, tetapi akan terus dilakukan secara berkelanjutan di masa depan. Sehingga akan menghasilkan generasi penerus bangsa yang berkualitas.  Kata Kunci: Pembentukan Karakter, Pendidikan Agama, Sumber Daya Manusia.